COMPOSITION AND FEATURES OF GEOGRAPHICAL DISTRIBUTION OF FAUNA OF ORIBATID MITES (ACARIFORMES, ORIBATIDA) IN THE TETHYS DESERT-STEPPE REGION - G. M. Abdurakhmanov; E. Z. Davudova; Yu. Yu. Ivanushenko; A. G. Abdurakhmanov (Юг России: экология, развитие, 2017)
Aim. The aim is to identify the similarities and differences of fauna of oribatid mites (Acariformes, Oribatida) in the Tethys desert-steppe region and analyze geographic relationships of the studied area.Methods. For the research, we used the materials collected for 5 years (2008-13) by the members of the stuff of the Department of Biology and Biodiversity (Grikurova A.A.) in the territory of the Republic of Dagestan. In addition, we referred to personal collections and publications including" Catalogue of oribatid mites of the Caucasus" by Shtanchaeva U.Ya., Subias L.S. To analyze the similarities of fauna of the Tethys region we made a comprehensive analysis based on Jaccard similarity coefficient.Results. As a result of the research we gave the composition of fauna, held a brief overview on oribatid mites and their resettlement and migration. In Tethys region, we identified 381 genera of oribatid uniting 1506 species, one third of which is endemic (501 species). Despite the fact that the fauna of the oribatid in the Caucasus is studied unevenly, the greatest variety of species is observed here. The smallest amount of diversity compared with the Caucasian species is observed in the Mediterranean countries and Central Asia, which shows the peculiarities of the genesis and geographic distribution.Conclusion. The dendrogram of similarity of the oribatid mites genera in the Tethys region demonstrates the tremendous role of coastal and island ecosystems of the Tethys Ocean, followed by the enrichment of the diversity as well as independent species shaping.